Separation simulation studies of large disturbance and high speed at low altitude. (October 2019) - Fan, Siyi; Fei, Wanghua; Guo, Pengfei; Zhang, Xuan; Yin, Geling; Zhang, Weiqiang; Shi, Rui; Ma, Ye
Abstract: Based on the secondary development function of ADAMS/VIEW, a parameterized simulation model of aircraft separation simulation is established by the external Fortran subroutine. A five-dimensional aerodynamic matrix is established in the program. The fourdimensional interpolation algorithm is used to calculate the aerodynamic values of the six components in real time, and the time-varying six-component aerodynamic data is provided for the aircraft and the lower stage. Based on the preliminary simulation analysis, based on the fully parameterized dynamic model, the variables such as angle of attack, side slip angle, pitch angular velocity, yaw angular velocity, roll angular velocity, aerodynamic force, aerodynamic moment, mass, and moment of inertia, which plays a role in predicting separation.